Integrated aquitard-aquifer flow with a mixed-type well-face boundary and skin effect. (March 2016) - Feng, Qinggao; Zhan, Hongbin
Highlights: The well-face is treated as a mixed-type, not a uniform flux boundary condition. The new solution unifies the existing solutions of flow in a (leaky) confined aquifer. The non-uniform flux effect diminishes at a distance larger than aquifer thickness. The effects of skin type and thickness on drawdown in the skin zone are significant. Abstract: A general analytical model describing groundwater flow to a partially penetrating well pumped at a constant rate in a leaky confined aquifer is developed. The model incorporates the effects of aquitard storage, aquifer anisotropy, wellbore storage and a finite well skin by treating the aquitard leakage as an aquitard-aquifer interface flow problem, and considers the well-face as a mixed-type or non-uniform flux (NUF) rather than a uniform flux (UF) boundary condition, which is novel. The solution is obtained using the Laplace transform coupled with separation of variables and discretization methods, followed by the numerical inverse Laplace transform. Moreover, the solution unifies some cases for flow to a partially penetrating well in a leaky confined aquifer including Perina and Lee (2006), Feng and Zhan (2015) and Hunt (2005) or confined aquifer including Chiu et al. (2007), Yang et al. (2006) and Hantush (1964). The newly developed NUF solution is compared with the UF solution. The NUF drawdown is larger than the UF drawdown at early time, while the NUF drawdown is smaller than the UF drawdown at intermediate and late times. The non-uniform flux along the well-face has significant impact on drawdown in the skin zone, while the UF solution can completely replace the NUF solution at a radial distance from the pumped well equaling to or greater than the aquifer thickness. The NUF and UF drawdowns for no skin case are remarkably smaller than that for the positive skin case and larger than that for the negative skin case. A thicker well skin results in a smaller drawdown in the skin zone.